2012
DOI: 10.1021/nl204561r
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Photonic Manipulation of Proteins and Other Nanomaterials

Abstract: The ability to controllably handle the smallest materials is a fundamental enabling technology for nanoscience. Conventional optical tweezers have proven useful for manipulating microscale objects but cannot exert enough force to manipulate dielectric materials smaller than about 100 nm. Recently, several near-field optical trapping techniques have been developed that can provide higher trapping stiffness, but they tend to be limited in their ability to reversibly trap and release smaller materials due to a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
158
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(160 citation statements)
references
References 30 publications
2
158
0
Order By: Relevance
“…The simple design and broadband nature of the waveguide-junctions do not impose sophisticated designs or wavelength-tunable lasers, and thus it could serve as a simple building block for "optical tweezers circuits." However, we remark that the trapping stiffness is low comparing to resonator-based particle traps [7,8]. We expect that by increasing the guided optical power and optimizing the tapered-junction design can help enhance the trapping stiffness.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The simple design and broadband nature of the waveguide-junctions do not impose sophisticated designs or wavelength-tunable lasers, and thus it could serve as a simple building block for "optical tweezers circuits." However, we remark that the trapping stiffness is low comparing to resonator-based particle traps [7,8]. We expect that by increasing the guided optical power and optimizing the tapered-junction design can help enhance the trapping stiffness.…”
mentioning
confidence: 86%
“…Microresonators and nanoresonators have also been employed for more functional particle manipulation devices [3][4][5][6][7][8]. However, the reported particle trapping on planar devices requires standing wave from resonators [7,8].…”
mentioning
confidence: 99%
“…145 This limitation to the tweezers is unfortunate, given the flexibility of manipulation it offers such as using the polarisation of the light to orient and align the objects. The precision of this placement can be improved though: for instance by coupling the laser with cavities in an optical resonator, it has been demonstrated that even 22 nm polymer particles can be immobilised in the cavities 148 ( see FIG. 15).…”
Section: Optical Nanomanipulationmentioning
confidence: 99%
“…First steps towards adding Raman spectroscopy to microcavity biosensing were taken recently: trapped particles on a ring resonator were utilized to enhance and collect the Raman signal of a model analyte [63]. Furthermore, the trapping of nanoparticles can find utility in size spectroscopy of particles, and enhancing measurement signals [64][65][66][67].…”
Section: Biodetection Mechanismsmentioning
confidence: 99%